KOMPOSISI KIMIA DAN KETAHANAN 12 JENIS ROTAN DARI PAPUA TERHADAP BUBUK KAYU KERING DAN RAYAP TANAH - Jasni; Gustan Pari; Titi Kalima (BRIN Publishing, 2016)
Rattan is spiny climbing palms, which is mostly utilized for furniture. This paper determines the chemical composition of 12 rattan species from Papua and its resistance against powderpost beetle (Dinoderus minutus Fabr.) and subterranean termite (Coptotermes curvignathus Holmgren). Chemical composition tested includes cellulose, lignin and starch contents. Cellulose content was determined by Norman and Jenkins method, while lignin content was determined based on the Indonesian National Standards (SNI 14-0492-1989 and SII-70-1979). Rattan resistance against powder post beetles and subterranean termites according to Indonesian Standard SNI 01-7207-2006. Results show that the highest cellulose content was found in somi-1 rattan (Calamus pachypus WJ Baker & al) of 52.82%, while the lowest cellulose content was found in longipina rattan (Calamus zebrianus Becc) which constitutes 42.29% cellulose content. The highest lignin content was recorded in endow rattan (Calamus zebrianus Becc) which was 33.37%, and the lowest was recorded in itoko rattan (Calamus vitiensis Warburg) which was about 21.00%. Two rattans studied were classified into class I against powder post beetle, and three of them were classified as class II. Four rattan species falls into class III and one species classified as class IV, and the other two species were classified as class V against powder post beetle. Based on the test against subterranean termites, three rattan species were classified as class I, five species as class II, two species as class III, one species as class IV, and one species as class V. Rattan species which was classified into III, IV, and V classes need to be preserved to enhance its service life.